1974
DOI: 10.1152/ajplegacy.1974.226.6.1344
|View full text |Cite
|
Sign up to set email alerts
|

Localization and function of medullary sites mediating vagal bradycardia in the cat

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Stimulation in this structure produces bradycardia (208), whereas stimulation of nucleus dorsalis vagus does not; destruction of the latter structure does not influence the bradycardia response to brain ischemia, for example (20). Stimulation in this structure produces bradycardia (208), whereas stimulation of nucleus dorsalis vagus does not; destruction of the latter structure does not influence the bradycardia response to brain ischemia, for example (20).…”
Section: The Medullary Vasomotor Areamentioning
confidence: 99%
“…Stimulation in this structure produces bradycardia (208), whereas stimulation of nucleus dorsalis vagus does not; destruction of the latter structure does not influence the bradycardia response to brain ischemia, for example (20). Stimulation in this structure produces bradycardia (208), whereas stimulation of nucleus dorsalis vagus does not; destruction of the latter structure does not influence the bradycardia response to brain ischemia, for example (20).…”
Section: The Medullary Vasomotor Areamentioning
confidence: 99%
“…Such a classification has been confirmed by tracer techniques in experimental animals (Bieger and Hopkins, 1987;Davis and Nail, 1984;Delgadao-Garcia et al, 1983;Gacek, 1975;Grelot et al, 1989;Hanamori and Smith, 1986;Hinrichsen and Ryan, 1981;Holstege et al, 1983;Hudson, 1986;Kalia and Mesulam, 1980b;Lobera et al, 1981;Portillo and Pasaro, 1988a,b;Schweizer et al, 1981;Sweazey and Bradley, 1986;Wallach et al, 1983;Yajima and Hayashi, 1983;Yoshida et al, 1980Yoshida et al, , 1981Yoshida et al, , 1982Yoshida et al, , 1984. Tracer techniques, however, have shown that the NA also contains cell bodies of preganglionic parasympathetic neurons concerned with the innervation of the heart (Bennett et al, 1979;Berger, 1980;deGroat et al, 1979;DiMicco et al, 1979;Ellenberger et al, 1983;Geis and Wurster, 1980a,b;Geis et al, 1981;Armour, 1979,1982;Kalia and Mesulam, 1980b;Kalia, 1981a;McAllen and Spyer, 1978;Nosaka et al, 1979;Stuesse, 1982;Stuesse and Fish, 1984;Stuesse and Powell, 1982;Thomas and Calaresu, 1974;Weiss and Priola, 19721, lungs (Bennett et al, 1982;Kalia and Mesulam, 1980b), esophagus …”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological data has shown that efferent vagal fibers to the heart originate not only in the DMNX but also in other nu clei in the dog [12] and cat [ 15,20,25]. Prob ably the most conclusive electrophysiologi cal evidence was provided by McAllen and Spyer [17,18] in which they demonstrated that only the neurons of the NA respond antidromically to stimulation of the cardiac branch of the vagus in cats.…”
Section: Discussionmentioning
confidence: 99%
“…Using retrograde degeneration techniques, investigators have reported that cardiac vagal fibers originate from the nucleus dorsalis in rabbits [11], monkeys [19] and pigeons [3], Fibers under going Wallerian degeneration following the destruction of the nucleus dorsalis were traced in the cardiac branches of the vagus nerve in cats [ 11. On the basis of electrophysiological studies, it has been reported that cardioinhibitory neurons are located in the DMNX of the pigeon [2], Other authors have reported that vagal efferent cardiac fibers originate not only in the DMNX but also in the nucleus ambiguous (NA) [ 15,25] and medial solitary nucleus (MSN) [18].…”
Section: Introductionmentioning
confidence: 99%